Mangrove replanting effort: A study on bruguiera cylindrica at Carey Island, Selangor. - Arbain Mokhtar; Azniza Abdul Ghani; Rozainah M. Z (Universiti Kebangsaan Malaysia, 2009)
Replanting of mangrove forest is considered as one of the best practices to protect coastal areas. In this study a total of 180 seedlings of Bruguiera cylindrica have been planted in the coastal area on Carey Island. Two sets of experiments with replanting patterns and replanting medium with 3 replicates under each treatment, using Completely Randomized Block Design were conducted. The survival rate of B. cylindrica was recorded every 2 weeks for 20 weeks. Result showed that the clumped distribution pattern was more suitable (20%) and that replanting directly on the ground method was the most successful in seedling survival (30%). However, ANOVA analysis showed that there was no significant difference between all the three replanting patterns as well as different media.